PENINGKATAN KETERAMPILAN MEMBACA PEMAHAMANAN MENGGUNAKAN MEDIA WORDWALL PADA SISWA KELAS IV C SDN KEBON JERUK 15 JAKARTA - Nurmala, Anna; Febrianti Yuli Satriyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve reading comprehension skills of narrative texts through the use of Wordwall media for fourth-grade students of class IV C at SDN Kebon Jeruk 15 Jakarta. The method used is Classroom Action Research (CAR) based on the Kemmis and McTaggart model. The researcher conducted two cycles consisting of planning, action, observation, and reflection stages. The research subjects were 30 students. The researcher used Wordwall as an interactive learning tool in the form of quizzes and educational games. The results of the study show an improvement in students' reading comprehension skills. The percentage of learning completeness increased from 14.2% in the pre-action stage to 37.9% in cycle I and significantly rose to 95.8% in cycle II. This indicates an improvement in learning outcomes in reading comprehension skills using Wordwall media for fourth-grade students of class IV C at SDN Kebon Jeruk 15 Jakarta.